Flood damages assessment – case study - M. ZELEŇÁKOVÁ; L. GAŇOVÁ (Aerul şi Apa: Componente ale Mediului, 2018)
The article deals with the resolution of the problem of managing flood risk with the aim of effective management focusing on reducing flood risks and thus increasing the measure of flood protection. It is elaborated in the sense of currently valid Slovak legislation in the field of flood protection, primarily according to the Directive 2007/60/EC on the assessment and management of flood risks. Assessment of potential flood damage is carried out for the town of Medzev, which was in the scope of preliminary assessment of flood risk in Slovakia evaluated as an area with an existing potentially significant risk of flood. Given the preliminary results, we can state that in the studied location of Medzev the construction of flood protection measures makes sense, mainly in relation to the protection of property.